Fiscal Equalisation and Natural Resources in Federal Systems - Fenna, Alan (John Curtin Institute of Public Policy, Curtin University of Technology, 2011)
Redistribution from wealthier to less-wealthy jurisdictions is a common if not virtually universal practice in federal systems and accords with some of the key principles of federalism. However, it easily becomes controversial or contested - particularly when resource revenues are at stake. This paper looks at the particular challenge posed by regionally-concentrated resource wealth in boom times and considers equity and efficiency arguments for a dilution or abolition of Australia's comprehensive system of horizontal fiscal equalisation put forward by 'donor' States and others.